Effect of Organic Matters And Water Stress On Performance of Rice in Vegetative Phase - Cut Nur Ichsan; Erida Nurahmi; Oktrya Rochmad; Bakhtiar Bakhtiar; Efendi Efendi; Sabaruddin Sabaruddin (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Drought become a major limiting factor in world cereal production. Various methods are used to solve this problem such as irrigation management by managing the soil moisture effectively for the  plants  to  grow  normally.  Another  way  to  improve  the  water  holding  capacity  with  the addition  of  organic  matter  in  soil.  Another  way  by  planting  drought  tolerant  rice  varieties. Drought-tolerant  rice  varieties  like  Inpago  8  with  various  doses  of  organic  matter  and  water stress at vegetative phase treatment done  to analyze  the  change of rice plant performance at the  vegetative  phase  of  the  rice  crop  due  to  drought  and  organic  matter  dose.    At  very  low water  content,  which  happened  repeatedly  during  the  vegetative  phase  causes  the  change  in root growth, plant height, length and width of rice leaf significantly